Student perceptions of project-based learning with a deep learning approach in vocational education - Intan Sari Ramadhani; Yuhendri Leo Vista (Global Econedu, 2026)
This study aimed to examine the effects of Project-Based Learning integrated with a Deep Learning approach on student engagement and digital archiving skills among vocational students based on their perceptions. A quantitative survey with an explanatory design was employed. The participants were 117 Office Management students at SMK Negeri 1 Painan selected through purposive sampling. Data were collected using validated and reliable questionnaires and analyzed using descriptive statistics and simple linear regression. Project-Based Learning with a Deep Learning approach significantly influenced student engagement (β = 0.963, t = 38.360, p < 0.001) and digital archiving skills (β = 0.851, t = 17.365, p < 0.001). Meaningful and contextual project-based learning is positively associated with higher student engagement and stronger perceived digital archiving competencies in vocational education.